2015
DOI: 10.1097/dss.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Early Treatment of Nevus of Ota With Low-Fluence 1,064-nm Q-Switched Nd

Abstract: This treatment was clinically effective and safe for early nevus of Ota using a low-fluence Q-switched Nd:YAG laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
2
18
1
1
Order By: Relevance
“…Prior studies have demonstrated that there is considerable variation in the laser parameters applied in the treatment of pigmentary diseases (usually between two and eight passes) [18][19][20]27]. Our results demonstrate that there is a positive correlation between the number of laser passes and pigmentation improvement.…”
Section: Discussionsupporting
confidence: 66%
“…Prior studies have demonstrated that there is considerable variation in the laser parameters applied in the treatment of pigmentary diseases (usually between two and eight passes) [18][19][20]27]. Our results demonstrate that there is a positive correlation between the number of laser passes and pigmentation improvement.…”
Section: Discussionsupporting
confidence: 66%
“…The possible factors that influence the results of the study were identified in the current literature: eyelid lesions, Tanino's classification, number of treatment sessions, a bilateral nevus, skin phototype, color of the lesion, and age at the first treatment261618. Our results revealed that the frequency of treatments was the key factor, which confirmed that more treatments would result in better outcomes, which is in agreement with other studies216.…”
Section: Discussionsupporting
confidence: 90%
“…There were no statistically significant differences between the cryotherapy-treated group and the others. Previously, topical hydroquinone has also been shown to not have significant benefits6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations